2018
DOI: 10.4081/gc.2018.7449
|View full text |Cite
|
Sign up to set email alerts
|

The traditional Chinese Baduanjin exercise for the enhancements in health of older adults: a narrative review

Abstract: Health debilitation negatively impacts the physical and psychiatric states of ageing persons, consequently increasing individual, familial, and social burdens. Physical exercise is an effective measure to cope with this problem, and Baduanjin, a traditional Chinese exercise, is one of the choices. This narrative review analyses 58 clinical studies, which indicate the efficacy of Baduanjin for the health of old adults, including in physiological refinement, bone diseases, cardiovascular and cardiopulmonary illn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 80 publications
(85 reference statements)
1
0
0
Order By: Relevance
“…Our MoCA score findings are in line with those of systematic reviews and meta-analyses, which have shown decreased age-related cognitive decline in older adults practicing qigong than in those participating in other interventions (Guo et al, 2016(Guo et al, , 2018Cheng, 2018;Zou et al, 2018;Chan et al, 2019). We found that the RBANS total score correlated strongly with the MoCA score, meaning that the RBANS is effective and valid for the assessment of cognitive function.…”
Section: Discussionsupporting
confidence: 89%
“…Our MoCA score findings are in line with those of systematic reviews and meta-analyses, which have shown decreased age-related cognitive decline in older adults practicing qigong than in those participating in other interventions (Guo et al, 2016(Guo et al, , 2018Cheng, 2018;Zou et al, 2018;Chan et al, 2019). We found that the RBANS total score correlated strongly with the MoCA score, meaning that the RBANS is effective and valid for the assessment of cognitive function.…”
Section: Discussionsupporting
confidence: 89%